Acute Biventricular Interaction in Pediatric Patients Implanted with Continuous Flow and Pulsatile Flow LVAD: A Simulation Study. Issue 5 (September 2016) - Di Molfetta, Arianna; Ferrari, Gianfranco; Iacobelli, Roberta; Fresiello, Libera; Pilati, Mara; Toscano, Alessandra; Filippelli, Sergio; Morelli, Stefano; Amodeo, Antonio
Abstract : Left ventricular assist devices (LVADs) are used to bridge pediatric patients till transplantation. However, the LVADs effects on right ventricular (RV) function are controversial. This work aims at studying the ventricular interdependency in the presence of continuous (c-) and pulsatile (p-) flow LVAD in pediatric patients using a lumped parameter model including the representation of the septum. Five pediatric patients' data were used to simulate patients' baseline. The effects on LV and RV functions, energetics, preloads and afterloads of different c-LVAD speeds, p-LVAD rate, p-LVAD systole duration, p-LVAD filling and ejection pressures were simulated. c-LVAD and p-LVAD unload the LV decreasing the LV external work and improving the LV ventriculo-arterial coupling and these effects are more evident increasing the c-LVAD speed and the p-LVAD rate. Continuous-LVAD and p-LVAD decrease the RV afterload, increase the RV ejection fraction and improve the RV ventriculo-arterial coupling. The changes in RV function are inversely proportional to the degree of the interventricular septum leftward shift that increased by increasing the LVAD contribution. The study of the interventricular interaction could lead to the development of a dedicated algorithm to optimize LVAD setting in pediatric population.